Protótipo para tomada de decisão em um ambiente controlado avaliando luminosidade, temperatura e presença, utilizando internet das coisas, para evitar desperdício de energia elétrica em uma instituição de ensino superior - Anjos, Rubervan Medeiros dos (Brasil, 2025)
With the increase in the search for energy efficiency and the growing use of technologies to optimize resources, IoT shows great potential in applications aimed at sustainable development. The main objective of this work was to create an IoT prototype capable of monitoring energy use in a classroom at a higher education institution, using PIR HC-SR501 presence sensors, DHT11 type temperature sensors and an LDR Photoresistor to measure luminosity, connected to an ESP32, capable of sending and receiving data collected in real-time online, the data is received and stored in the cloud, through the Firebase platform. The methodology was structured in three phases: in the first phase, the research problem and the needs of the monitoring system were defined. In the second phase, the system to collect data was developed, as well as its physical part, with assembly and docking in a cabinet made with a 3D printer, integrating them with a web monitoring interface. Finally, in the third phase, the prototype's performance was analyzed, evaluating the accuracy of the data collected and the efficiency of transmitting information in real time. The prototype developed was capable of monitoring the use of lamps and air conditioning in the environment. The proposed prototype offers a viable and efficient solution for monitoring energy use in higher education institutions, allowing for more detailed and accurate management of energy resources.